2018
DOI: 10.15226/2374-6904/5/2/00171
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Bone Remodelling and Bone Metabolism Markers

Abstract: Sedentary lifestyle is associated with detrimental health effects on bone. Risk of fracture and lower bone mineral density (BMD) are increased among people with lower physical activity level. The onset of osteoporosis does not occur immediately. Instead, it slowly progresses throughout the years. The ideal approach and easier way to prevent or delay the onset of osteoporosis should focus on changing one’s lifestyle by including higher amount of physical activity. Exercise or higher amount of physical activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…On the one hand, it has been shown that ALP changes can demonstrate the bone formation process. Sahrir, in their review study, have shown that 32 weeks of aerobic exercise with a minimum 30-joule workload in a week was necessary to increase skeletal mass in rats (6). In order to better understand the results, it will be announced that two factors -extreme severity of exercise and Calcium consumption-have induced the progressive augmentation of this process, as it has been shown that Calcium consumption increases the speed of ALP activity (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, it has been shown that ALP changes can demonstrate the bone formation process. Sahrir, in their review study, have shown that 32 weeks of aerobic exercise with a minimum 30-joule workload in a week was necessary to increase skeletal mass in rats (6). In order to better understand the results, it will be announced that two factors -extreme severity of exercise and Calcium consumption-have induced the progressive augmentation of this process, as it has been shown that Calcium consumption increases the speed of ALP activity (22).…”
Section: Discussionmentioning
confidence: 99%
“…They studied young men while our research was on older women. This difference between the two groups of participants will be justified considering their age average, as a bone reaction to exercise varies in different age ranges (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, bone formation and resorption allow for response to dynamic mechanical forces and also assist in functional and metabolic demands. Nevertheless, in some specific conditions, homeostasis at rest can be altered by physiological stimuli as observed during exercise and load, but also associated with pathologies such as aging-related osteoporosis, metabolic diseases, cancer, and therapeutic interventions [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Micro-cracks can cause a stress reaction (e.g., oedema) or propagate and merge into a stress fracture (Burr et al, 1997;Donahue et al, 2000;Taylor & Lee, 2003;Wyon et al, 2014). The bone remodelling process which can repair damage by resorbing damaged bone tissue and forming new bone is stimulated by applied mechanical stress (Maïmoun & Sultan, 2011;Ooi & Sahrir, 2018).…”
mentioning
confidence: 99%